2013
DOI: 10.3233/cbm-130361
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of integrin αv in the human nasopharyngeal carcinoma associated with metastasis and progression

Abstract: All these findings suggest that overexpression of integrin αv is closely associated with metastasis and progression of NPC. Therefore, we can speculate that integrin αv could be effective prognostic markers in the future for individualized treatment of patients with NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
(22 reference statements)
1
7
0
1
Order By: Relevance
“…Previous studies have identified many different genes that are involved in metastasis of NPC, accelerating or suppressing metastasis by a mechanism of cooperative or inhibitive interactions between genes, such as LMP1 [18], NGX6 [19][20], Fibulin-5 [21], IntergrinαV[22], MIF and DJ-1[23] and so on. Our previous studies also confirmed that high expression of p-eIF4E and p-Mnk1 played a critical role in promoting invasion and metastasis and related with the poor prognosis of NPC patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified many different genes that are involved in metastasis of NPC, accelerating or suppressing metastasis by a mechanism of cooperative or inhibitive interactions between genes, such as LMP1 [18], NGX6 [19][20], Fibulin-5 [21], IntergrinαV[22], MIF and DJ-1[23] and so on. Our previous studies also confirmed that high expression of p-eIF4E and p-Mnk1 played a critical role in promoting invasion and metastasis and related with the poor prognosis of NPC patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Nakada et al [23] reported that ITGα3 is over-expressed in glioma stem-like cells and promotes invasion. Furthermore, evidence shows that overexpression of ITGαv is closely associated with the metastasis and progression of some cancers [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…The expression of αv integrin subunits is correlated with lymphatic metastasis of laryngeal and hypopharyngeal carcinoma, although the associated integrin β subunit that plays the major role in SCC aggressiveness was not identified [53]. In nasopharyngeal carcinoma, expression levels of integrin αv mRNA and protein are also correlated with tumour size and lymph node spread, and were significantly higher in nasopharyngeal carcinoma tissues than in non-neoplastic inflammation tissues from the same region [54]. …”
Section: Integrins In Hnsccmentioning
confidence: 99%
“…Since expression of the αv and β1 subunits have been associated with proliferation [53] and metastasis [51,53,54,95,107], αvβ3 [65] and αvβ6 [80,84] associated with proliferation and invasion, targeting one or more of these receptors appears to be an attractive strategy to reduce either tumour growth or dissemination. With the exception of cilengitide, very limited preclinical studies have taken place so far [80,88,107].…”
Section: Applications Of Integrin-targeted Agentsmentioning
confidence: 99%